Recommendations for Off-Label Drug Use in Ophthalmology in China: A Clinical Practice Guideline - Li, Guangyao; Wang, Ningli; Zhang, Yu; Wei, Wenbin; Lu, Hai; Zhai, Suodi; Zhang, Chao (Frontiers in Pharmacology, 2022)
Off-label drugs use is widespread in ophthalmology due to the delay in drug approvals and package inserts update. It has been found to vary among different medical institutions in China, leading to safety problems since inappropriate use. Guidance is urgently needed regarding how best to use the drugs for unapproved indications and routes of administration. We aimed to develop an evidence-based guideline to guide off-label drugs used in ophthalmology in China. The practice guideline was developed by the Hospital Pharmacy Professional Committee, Chinese Pharmaceutical Association, following the WHO handbook for guideline development. The guideline was initially registered in the International Practice Guidelines Registry Platform (IPGRP-2021CN096). The clinical questions included in the guideline were identified through a three-round Delphi vote. Databases search was performed in PubMed, Embase, the Cochrane Library, ClinicalTrials.gov, Chinese National Knowledge Infrastructure, and WanFang Database from their inception to Mar 31, 2021. Systematic reviews and meta-analyses for each clinical question were conducted individually to synthesize available scientific evidence. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach was used to assess the quality of evidence and grade the recommendations' strengths. The multidisciplinary guideline groups were set up, including ophthalmologists, pharmacists, methodology experts, pharmacologists, pharmacoeconomists, and lawyers. The guideline identified 25 clinical questions included. A total of 35 systematic reviews, including 26 conducted by the systematic review group and 8 high-relevance published within two years, were referred to address these questions. Finally, the guideline presented 32 recommendations addressing 25 clinical questions, involving 5 strong recommendations and 27 weak recommendations for the treatment of ocular fundus, corneal disease, glaucoma, and endophthalmitis. Current evidence from clinical studies supports the off-label drugs used in ophthalmology. We developed an evidence-based guideline using a rigorous multidisciplinary approach to guide these usages in route clinical practice.